(untitled) (Journal of Hama University, 2019)
The aim of this study is to investigate the effect of reduction on pH value on release of nickel and chromium ions from orthodontic wires. The study sample consisted of 80 orthodontic wires divided into two equal groups (each group consisted of 10 superelastic nickel-titanium wires, 10 heat-activated nickel-titanium wires, 10 stainless steel, and nickel-chrom-cobalt wires). The wires immersed in artificial saliva of different pH values (5-7) during 1 month. Concentration of ions release were measured using a graphite furnace absorption spectrophotometer (AAS). Result: The results of this study showed significant differences in nickel and chromium ions concentrations between the four studied types of wires (p˂0.05). The largest quantity of nickel and chromium ions was released from nickel-chrom-cobalt wires. Study found that the change in pH had a strong effect on the release of ions from wires. Conclusion: concentrations of nickel and chromium released from the orthodontic wires were far below the toxic dose to human, and the low pH resulted in an increase in the release of nickel and chromium ions from wires.